Social Movement Gains and Losses: Dilemmas of Arena Creation - Elliott-Negri, Luke; Jabola-Carolus, Isaac; Jasper, James; Mahlbacher, Jessica; Weisskircher, Manès; Zhelnina, Anna (PARTECIPAZIONE E CONFLITTO, 2021)
Social movements never entirely win or lose, nor do they suddenly appear or disappear. Just as their component parts recombine and continue in other forms, so movements have dozens of impacts of various kinds. To make sense of this complexity we propose examining the outcomes of political interactions for a variety of players (including individuals) across a range of arenas. Given the acknowledged tradeoffs and dilemmas of collective action, we would expect packages of outcomes to appear together sometimes; for example, gains in street mobilization may lead to losses in the form of a damaged reputation or police repression. The first step to explaining such patterns is to identify and name them. We examine one of these outcome patterns, the arena-ownership package, through the case of Seattle’s historic 15 per hour wage law passed in 2014, the first ever in a major U.S. city. The players who crafted the bill included an avowed Socialist, the owner of Seattle’s iconic Space Needle tower, many representatives of the city’s labor movement, and the newly elected Democratic Mayor Ed Murray. These diverse players moved through a series of complex arenas to arrive at the legislative outcome. In this case, we find players who create new arenas, rather than only using already-existing arenas. This move is associated with a typical package of gains and losses: increased control for the player on the one hand, but corresponding losses and risks—the alienation of excluded players and increased perception of responsibility. The creating player is blamed for the arena’s failures as well as credited with its successes.